Hubungan kadar troponin t (TnT) dan creatinin kinase-myocardial band (CK-MB) pada pasien infark miokard akut (IMA) di Rumah Sakit Umum Pusat (RSUP) Sanglah Denpasar - Santika Dewi, Ni Gusti Ayu Putu Lestari; Lestari, AA Wiradewi; Yasa, I Wayan Putu Sutirta (E-Jurnal Medika Udayana, 2018)
Acute Myocardial Infarction (AMI) is a condition of myocardial necrosis due to the imbalance between supply and demand of oxygen to the heart muscle. The increases level of cardiac biomarkers such as troponin T (TnT) and creatinin kinase-myocardial band (CK-MB) are important criteria in diagnosing patients with AMI particularly in patients with atypical chest pain and difficulty avoiding the bias of the recording and ECG reading. The purpose of this study is to determine the correlation between TnT and CK-MB levels in AMI patients. This study was a cross sectional observational analytic study that enrolled 153 patients with AMI by consecutive sampling period January 1st, 2014 – December 31th, 2014. The data that obtained in this research were secondary data of AMI patients who checks TnT and CK-MB from patient’s medical record and clinical pathology laboratories Sanglah Hospital, Denpasar. In this study showed that AMI is more common in men (85%) and most at the age of 55-64 years (37,3%) with elevated levels of TnT (77,8%) and CK-MB(73,9%). From the analysis of Spearman correlation test showed a significant correlation between TnT and CK-MB levels with p = 0.0001 and the correlation coefficient (r) is 0.622. Therefore, this study concludes that there is a significant correlation between TnT and CK-MB levels in patients with AMI at Sanglah Hospital, Denpasar. Keywords: Acute Myocardial Infarction, Troponin T (TnT), Creatinin Kinase-Myocardial Band (CK-MB)